Research on the distributed capacitance for high-voltage key components on CRAFT NNBI - LIU, Bo; LIU, Zhimin; JIANG, Caichao; LIU, Sheng; PAN, Junjun; CHEN, Shiyong; WEI, Wei; QU, Yuchen; LIANG, Lizhen; BAI, Ruoxin; XIE, Yuanlai (Plasma science & technology, 2025)
The negative ion based neutral beam injector (NNBI) with a beam energy of 400 keV is one of the subsystems at the Comprehensive Research fAcility for Fusion Technology (CRAFT) in China. The distributed capacitance of the high-voltage components is an important basis for the design of surge suppression devices at CRAFT NNBI. This study conducted calculations of distributed capacitance for the key components, including the high-voltage deck, transmission line and isolation transformer in the power supply system using the finite element method. The relationship between the high-voltage deck (HVD) distributed capacitance and the distance from the wall is discussed. The differences in distributed capacitance and energy storage between non-coaxial and coaxial transmission lines are also debated. Finally, the capacitance between the primary and secondary windings of the −400 kV isolation transformer, as well as between the secondary winding and the oil tank casing, was calculated.